Tourism Satisfaction Analysis of Tourism Packages as Tourism Products in Paksebali Village, Klungkung, Bali - Pantiyasa, I Wayan; Prabawati, Ni Putu Diah (Institut Pariwisata dan Bisnis Internasional, 2020)
The purpose of this study was to determine the level of satisfaction of tourists who visit and enjoy tour packages as a product of the tourism village of Paksebali, Klungkung, Bali. Data were collected by interviewing, observing, and distributing questionnaires to 100 tourists (incidental sampling). Data were analyzed using qualitative and quantitative descriptive analysis techniques through Index Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The result of the study is the tourists are satisfied. The indicators considered important by tourists are the friendliness of tour guides and the performance that exceeds their expectations. Indicator considered less important by tourists are the procedures for serving food and beverages, and the price suitability for tour packages. An indicator considered less important by tourists and felt too excessive is the cleanliness of the village environment. The tourists also hope that the tour time will be extended so they can be more involved in community activities.